When can government subsidize research joint ventures? Politics, economics, and limits to - Cohen, Linda R. (American Economic Review, 1994)
Research joint ventures (RJV's) between private firms and government bureaus play a central position in the Clinton Administration's R&D strategy to promote productivity and of American firms. The government's role in the programs varies from subsidizing private projects to providing the expertise and facilities of the federal research laboratories. A substantial literature now exists that investigates the economic efficiency of private RJV's. The purpose of this paper is to expand the debate to consider the conditions under which the government will choose to subsidize RJV's and whether these conditions are likely to yield desirable economic results. It is useful to characterize the government as a consortium member who differs from the private venturers in several critical ways. First, these programs are based on the presumption that private firms are far better than government at choosing projects with commercial merit. Even in those programs where the government contributes scientists and facilities, industry partners usually have primary responsibility for initiating projects. Second, the objective function of the government differs from industry members. Indeed, it is in part because government actors have goals other than competitiveness that these programs are intended to keep government bureaucrats at arm's length from technical choices. Finally, the financial contribution of the government is usually a set share of the total bill. Introducing this form of subsidy changes the research investment strategies employed by a joint venture, and the incentives facing firms either to participate in a consortium or to oppose its establishment. The basic premise of this analysis is that a subsidized joint venture will persist only when all members, including the government, are satisfied. A viable policy depends on economic consequences to member firms, and to the extent that they have access to policy-making, to nonmember firms and consumers. Furthermore, some of the relevant consequences follow predictably from market and technology characteristics.